Congruency Effect During Attention Network Task for Electroencephalogram-based Alpha Neurofeedback Training - Danyal, Mahmood; Humaira, Nisar; Siti Atiyah, Ali (2024)
Neurofeedback Training (NFT) using Electroencephalogram (EEG) allows individuals to selfregulate the activity of their brain non-invasively. NFT improves an individual's attention levels but the effect of congruency (alternation and repetition) on brain activity is still unknown. This study aimed to investigate the congruency effect of attention on 50 healthy participants (NFT Group: 25, Control Group: 25) after long-term alpha NFT. We examined changes in functional connectivity and band power within the alpha band. During the Attention Network Task (ANT), each participant's EEG was recorded with congruent and incongruent stimuli in a pseudorandom order. A pre to postNFT was increased in alpha band peak power within the temporal, parietal, and occipital regions, indicating the effectiveness of NFT. Additionally, there was an increase in task-related peak functional connectivity. However, the congruency did not affect the strength of functional connections between different brain regions. Stimuli alternation had a greater effect on alpha band power and connectivity modulation than stimuli repetition.